Mathematical Modelling and Numerical Simulation of Dendrite Growth Using Phase-Field Method with a Magnetic Field Effect (Communications in Computational Physics, 2014)
In this paper, we present a new model developed in order to analyze phenomena which arise in the solidification of binary mixtures using phase-field method,which incorporates the convection effects and the action of magnetic field. The modelconsists of flow, concentration, phase field and energy systems which are nonlinearevolutive and coupled systems. It represents the non-isothermal anisotropic solidification process of a binary mixture together with the motion in a melt with the applied magnetic field. To illustrate our model, numerical simulations of the influenceof magnetic-field on the evolution of dendrites during the solidification of the binarymixture of Nickel-Copper (Ni-Cu) are developed. The results demonstrate that thedendritic growth under the action of magnetic-field can be simulated by using ourmodel.